Planetary nebulae and how to find them: A concise review - Parker , Quentin A. (Frontiers in Astronomy and Space Sciences, 2022)
This review is intended to provide useful background and information on how we find, detect and compile Planetary Nebulae PNe candidates and verify them. It also presents a summary of the current known Galactic PN population and their curation in the Hong Kong/ AAO/ Strasbourg/ H-alpha planetary nebulae catalogue, HASH. It is a simple introduction for anyone interested in working with Planetary Nebulae, including postgraduate students entering the field and for more general interest too.